Lightweight AlCuFeMnMgTi High Entropy Alloy with High Strength-to-Density Ratio Processed by Powder Metallurgy - Chae, Myoung Jin; Sharma, Ashutosh; Oh, Min Chul; Ahn, Byungmin (Metals and Materials International, 2021)
Abstract: In this study, we synthesized a new Al16.6Cu16.6Fe16.6Mn16.6Mg16.6Ti16.6 lightweight high entropy alloy (LWHEA) by high energy ball milling and spark plasma sintering (SPS). The effect of milling time (15, 30, 45, and 60 h) and SPS conditions (600 and 700 °C) on microstructure, hardness, and density of LWHEAs were studied. The results showed that milled LWHEA is base centered cubic (BCC) structured, consisting of dual BCC1/BCC2 matrix with dispersed minor Cu2Mg precipitates and Ti. After SPS of milled samples, the BCC2 phase fraction was increased gradually. The distribution of Ti was uniform up to 45 h milled sample SPSed at 600 °C. However, porosity was built up beyond 45 h milling and higher SPS temperature (700 °C). The presence of finer secondary phases in the HEA matrix contributes to the dispersion hardening. The optimum microhardness and density of LWHEA AlCuFeMnMgTi were around 770 HV and 4.34 g cm− 3 which is superior to other conventional alloys such as Al or Ti-based alloys. Graphic Abstract: [Figure not available: see fulltext.].
Keywords: Conventional alloys; Density ratio; High strength; High-energy ball milling; Milling time; Phase fractions; Secondary phasis; Ti based alloy; High entropy alloy; Lightweight; Microstructure; Powder metallurgy; Spark plasma sintering